Highly Regioselective Synthesis of 3,5-Substituted Pyrazoles from Bromovinyl Acetals and N-Tosylhydrazones - Westermeyer, Anne; Llopis, Quentin; Guillamot, Gérard; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie (Synlett, 2020)
A regioselective synthesis of 3,5-disubstituted pyrazoles was achieved by 1,3-dipolar cycloaddition of diazo compounds, generated in situ from N-tosylhydrazones, with unactivated bromovinyl acetals, which served as alkyne surrogates. The reaction tolerated N-tosylhydrazones bearing various substituted benzylidene groups, and a range of 3,5-disubstituted pyrazoles were obtained in yields of up to 92%.
Keywords: pyrazoles; 1,3-dipolar cycloaddition; bromovinyl acetals; tosylhydrazones